PENGARUH KOMPETENSI, PEMANFAATAN TEKNOLOGI INFORMASI, KOMITMEN DAN REVISI ANGGARAN PADA EFEKTIVITAS PENGELOLAAN ANGGARAN UNIVERSITAS UDAYANA - Sukarta, I Wayan; Badera, I Dewa Nyoman; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aimed to get empirical evidence of the influence of human resources competence, utilization of information technology, organizational commitment and budget revision on the effectiveness of Udayana University budget management. Data source used are primary data obtained through questionnaires. The respondents were all over the existing budget management officer of Udayana University in 2016 as many as 156 peoples. Data analysis technique used multiple linear regression. The analysis showed that the human resources competencies positive influence on the effectiveness of budget management, utilization of information technology positive influence on the effectiveness of budget management, organizational commitment positive influence on the effectiveness of budget management and budget revision positive influence on the effectiveness of Udayana University budget management.
Keywords: competence, utilization of information technology, commitment, budget revision, effectiveness of budget management